1990
DOI: 10.1007/bf02030506
|View full text |Cite
|
Sign up to set email alerts
|

Open lung biopsy of patients with rheumatoid arthritis

Abstract: In order to shed light on the histological changes occurring in the lungs of patients with rheumatoid arthritis (RA), we scrutinized an open lung biopsy file of 199 patients and selected the patients with RA. The histopathological patterns observed were: pulmonary rheumatoid nodules (4 cases, including one with rheumatoid pneumoconiosis); usual interstitial pneumonia (UIP) (2 cases); desquamative interstitial pneumonia (2 cases); bronchiolitis obliterans with patchy organizing pneumonia (2 cases); follicular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 27 publications
2
26
0
1
Order By: Relevance
“…To evaluate IP activity, open lung biopsy [6,13,28], Ga-67 scintigram [13], and BAL [4,13,24] are considered reliable examinations. However, it is practically impossible to apply these examinations repeatedly because of their side effects.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate IP activity, open lung biopsy [6,13,28], Ga-67 scintigram [13], and BAL [4,13,24] are considered reliable examinations. However, it is practically impossible to apply these examinations repeatedly because of their side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of patients with RA-ILD have suggested a relationship of the UIP pattern to survival [20,[28][29][30]. YOUSEM et al [28] described 40 patients with RA-ILD, five of whom had a UIP pattern on surgical lung biopsy.…”
Section: Uip Pattern and Survivalmentioning
confidence: 99%
“…Four of the UIP-pattern patients died during follow-up, whereas only one of the non-UIP-pattern patients died. HAKALA et al [29] reported on 24 patients with RA-ILD. Two patients died; both had honeycombing present on surgical biopsy.…”
Section: Uip Pattern and Survivalmentioning
confidence: 99%
“…The clinical outcome of CTD-OP has not been well defined, even though various studies have reported a worse prognosis, a lower complete recovery rate, and a tendency towards higher recurrence rates as compared to the idiopathic form [121,123]. In RA, OP represents up to 10-15% of any ILD involvement and is often observed during the follow-up of joint-associated symptoms, but in rare cases it can predate the development of joint manifestations or serological conversion, which may lead to underdiagnosis and missing of the link between OP and underlying but early and undiagnosed RA [123,125,126,127]. In DM-PM, OP is an even more common manifestation, with its reported prevalence approaching 20% [125,128,129].…”
Section: Op and Afopmentioning
confidence: 99%